# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime }+y^{\prime }+3 y = \left (1-\operatorname {Heaviside}\left (t -2\right )\right ) {\mathrm e}^{-\frac {t}{10}+\frac {1}{5}} \sin \left (t -2\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = \sin \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+16 y = t
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = \frac {1+x}{x -1}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{2} y^{\prime \prime } = 8 x^{2}
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }+8 y = {\mathrm e}^{-x^{2}}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+3 x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 = x
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+2 = \sqrt {x}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+4 y^{\prime } = 18 x^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime } = 2 y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime } = 8 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime } = y^{\prime }-2 x^{2} y^{\prime }
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+2 x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 4 x \sqrt {y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } y^{\prime \prime } = 1
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime } = -{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime } = {y^{\prime }}^{2}-y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }-{y^{\prime }}^{2} = 6 x^{5}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }-{y^{\prime }}^{2} = y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 2 y^{\prime }-6
\] |
✓ |
✓ |
|
\[
{}\left (-3+y\right ) y^{\prime \prime } = 2 {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime } = 9 \,{\mathrm e}^{-3 x}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime } = {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}3 y y^{\prime \prime } = 2 {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}\sin \left (y\right ) y^{\prime \prime }+\cos \left (y\right ) {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }+{y^{\prime }}^{2} = 2 y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{2} y^{\prime \prime }+y^{\prime \prime }+2 y {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 4 x \sqrt {y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } y^{\prime \prime } = 1
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime } = {y^{\prime }}^{2}-y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }-y^{\prime } = 6 x^{5}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }-{y^{\prime }}^{2} = y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime } = 2 {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}\left (-3+y\right ) y^{\prime \prime } = {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime } = 9 \,{\mathrm e}^{-3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = y^{\prime } \left (y^{\prime }-2\right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+4 y^{\prime } = 18 x^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime } = 2 y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime } = 8 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+2 y^{\prime } = 6
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime } y^{\prime \prime } = {y^{\prime }}^{2}-1
\] |
✓ |
✓ |
|
\[
{}3 y y^{\prime \prime } = 2 {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }+2 {y^{\prime }}^{2} = 3 y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = -y^{\prime } {\mathrm e}^{-y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = -2 x {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = -2 x {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = -2 x {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = -2 x {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 2 y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 2 y y^{\prime }
\] |
✗ |
✓ |
|
\[
{}y^{\prime \prime } = 2 y y^{\prime }
\] |
✗ |
✓ |
|
\[
{}y^{\prime \prime } = 2 y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x^{2} y^{\prime }-4 y = x^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x^{2} y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x^{2} y^{\prime } = 4 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x^{2} y^{\prime }+4 y = y^{3}
\] |
✗ |
✗ |
|
\[
{}\left (1+y\right ) y^{\prime \prime } = {y^{\prime }}^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 2 y^{\prime }-5 y+30 \,{\mathrm e}^{3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-5 y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-10 y^{\prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-6 x y^{\prime }+12 y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }-x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-\left (4+\frac {2}{x}\right ) y^{\prime }+\left (4+\frac {4}{x}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y^{\prime \prime }+x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-\frac {y^{\prime }}{x}-4 x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+\left (2+2 x \right ) y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right )^{2} y^{\prime \prime }-2 \sin \left (x \right ) \cos \left (x \right ) y^{\prime }+\left (\cos \left (x \right )^{2}+1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-2 x y^{\prime }+\left (x^{2}+2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+3 y = 9 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+8 y = {\mathrm e}^{4 x}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }-y = \sqrt {x}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-20 y = 27 x^{5}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+\left (2+2 x \right ) y^{\prime }+2 y = 8 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y^{\prime \prime }+x y^{\prime }-y = \left (1+x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }-6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }+4 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }-y^{\prime }+4 x^{3} y = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right )^{2} y^{\prime \prime }-2 \left (1+x \right ) y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }-y^{\prime }+4 x^{3} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }-3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-10 y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|